2012
DOI: 10.1111/j.1872-034x.2012.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of radiofrequency ablation for hepatocellular carcinoma in the caudate lobe of the liver

Abstract: We were able to safely treat HCC located in the caudate lobe by RFA. However, there was a high incidence of local recurrence, presumably because of the heat sink effect of the inferior vena cava and the restricted puncture approach. We should pursue a revised method to reduce local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Driving a CT or US guided percutaneous RFA needle for an ill location of tumor is difficult so parallel disposition of the US probe and needle is the widely accepted. 20 However, in our study, under the laparoscope, we placed the electrode needle nearly vertical the US probe. Our own experiences indicated that laparoscope could provide a more appropriate approach in handling ill-located caudate tumor due to better visualization of tumor and less restriction of electrode compared to the CT-guided RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Driving a CT or US guided percutaneous RFA needle for an ill location of tumor is difficult so parallel disposition of the US probe and needle is the widely accepted. 20 However, in our study, under the laparoscope, we placed the electrode needle nearly vertical the US probe. Our own experiences indicated that laparoscope could provide a more appropriate approach in handling ill-located caudate tumor due to better visualization of tumor and less restriction of electrode compared to the CT-guided RFA.…”
Section: Discussionmentioning
confidence: 99%
“…We found the overall survival rates were not significantly higher in younger than in elderly HCC patients. Since previous report showed that the 4-year cumulative local recurrence rate after RFA in the caudate group and the non-caudate group was 22.3% and 4.5%, respectively ( P <0.001) [10], we also determined whether or not RFA combined with TACE for HCC treatment is as effective for HCC in the caudate lobe as it is for HCC at other sites in the liver. We did not find any significant differences between the caudate group and the non-caudate group and the overall survival rates were not significantly changed between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates for patients who achieved a complete response by RFA are comparable to that of patients treated by hepatic resection [7], [8]. Therefore, RFA has been widely used as a first-line therapy for patients with small HCC who could not receive surgical resection or LT in the recent years [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…reported that the local recurrence rate after RFA was significantly higher in the caudate group (22.3%) than in the non‐caudate group (4.5%). Furthermore, they suggested that the most significant factor associated with an insufficient or no safety margin was a location in the vicinity of the inferior vena cava . One of the mechanisms is heat loss, well known as the HSE of the inferior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous radiofrequency ablation (RFA) therapy is a useful alternative to surgical resection. Some previous studies have reported the efficacy of the percutaneous procedure, although it was technically difficult to place the electrode for the RFA procedure in the caudate lobe . Percutaneous ablation of a nodule in the caudate lobe can be carried out safely by proper selection of the puncture route with monopolar RFA .…”
Section: Introductionmentioning
confidence: 99%